Airflow Obstruction and Cardio-metabolic Comorbidities. (4th March 2019) - Triest, Filip J.J.; Studnicka, Michael; Franssen, Frits M.E.; Vollmer, William M.; Lamprecht, Bernd; Wouters, Emiel F.M.; Burney, Peter G. J.; Vanfleteren, Lowie E.G.W.
Abstract: Chronic obstructive pulmonary disease (COPD) is characterized by airflow obstruction and often co-exists with cardiovascular disease (CVD), hypertension and diabetes. This international study assessed the association between airflow obstruction and these comorbidities. 23, 623 participants (47.5% males, 19.0% current smokers, age: 55.1 ± 10.8 years) in 33 centers in the Burden of Obstructive Lung Disease (BOLD) initiative were included. 10.4% of subjects had airflow obstruction. Self-reports of physician-diagnosed CVD (heart disease or stroke), hypertension and diabetes were regressed against airflow obstruction (post-bronchodilator FEV1 /FVC < 5th percentile of reference values), adjusting for age, sex, smoking (including pack-years), body mass index and education. Analyses were undertaken within center and meta-analyzed across centers checking heterogeneity using the I 2 -statistic. Crude odds ratios for the association with airflow obstruction were 1.42 (95% CI: 1.20–1.69) for CVD, 1.24 (1.02–1.51) for hypertension, and 0.93 (0.76–1.15) for diabetes. After adjustment these were 1.00 (0.86–1.16) (I 2 :6%) for CVD, 1.14 (0.99–1.31) (I 2 :53%) for hypertension, and 0.76 (0.64–0.89) (I 2 :1%) for diabetes with similar results for men and women, smokers and nonsmokers, in richer and poorer centers. Alternatively defining airflow obstruction by FEV1 /FVC < 2.5th percentile or 0.70, did not yield significant other results. In conclusion, the associations of CVD and hypertension with airflow obstruction in the general population are largely explained by age and smoking habits. The adjusted risk for diabetes is lower in subjects with airflow obstruction. These findings emphasize the role of common risk factors in explaining the coexistence of cardio-metabolic comorbidities and COPD.